1992
DOI: 10.1002/lipi.19920940905
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Phase Transitions in Tripalmitin due to the Presence of Dipalmitin, Sorbitan‐Monopalmitate or Sorbitan‐Tripalmitate

Abstract: The effects of diglycerides, sorbitan-monoesters and sorbitantriesters on triglyceride polymorphic transitions have been examined.Earlier reported effects of retardation of + p transitions due to the presence of asymmetric diglycerides were found to be the same from the racemic and antipode forms. The a * p and p' + p transitions of tripalmitin (PPP) were followed when sorbitan-monopalmitate (SMP), sorbitan-tripalmitate (STP), or dipalmitate (DP) were present. The STP gave a slightly stronger reduction in tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…The type of emulsifier used in the formulation may, however, not only affect the physical stability of the dispersion and the range of possible administration routes. In bulk triglycerides, admixture of different types of surfactants can have pronounced effects on the kinetics of polymorphic transitions after crystallization 6–8. An influence of the emulsifier composition on the polymorphism of triglycerides has also been observed for colloidal triglyceride dispersions 9.…”
Section: Introductionmentioning
confidence: 95%
“…The type of emulsifier used in the formulation may, however, not only affect the physical stability of the dispersion and the range of possible administration routes. In bulk triglycerides, admixture of different types of surfactants can have pronounced effects on the kinetics of polymorphic transitions after crystallization 6–8. An influence of the emulsifier composition on the polymorphism of triglycerides has also been observed for colloidal triglyceride dispersions 9.…”
Section: Introductionmentioning
confidence: 95%
“…It could, for example, be shown that the stabilization using phospholipids in combination with other surfactants results in a higher stability than using phospholipids alone [13]. In addition, emulsifiers may affect the polymorphic transitions (as also described for bulk materials [14][15][16]), the crystallization temperature, and the morphology of SLN [5-7, 9, 16]. For example, the use of saturated phospholipids increases the crystallization temperature, decreases the transition velocity and consequently increases the stability of the crystallized a-modification.…”
Section: Specific Characteristics Of Slnmentioning
confidence: 99%
“…One can add food emulsifiers that retard transformations from the β to the β form (Aronhime et al, 1988;Garbolino et al, 2005;Sato and Kuroda, 1987). One can add diacylglycerols (Mohamed and Larsson, 1992), or one can use interesterification techniques with different fats and oils (Chrysan, 2005).…”
Section: Fats In Water-in-oil Emulsionsmentioning
confidence: 99%